Endovascular Management of a Rare Case of a True Facial Artery Aneurysm: A Case Report - jha, Manvendu; Nandan Tripathy, Girija; Vembu, Anand (Medical Journal of Shree Birendra Hospital, 2022)
True aneurysms of the facial artery are rare and their management protocol is not defined. There are only eight cases reported in the literature. Here we report a case of true aneurysm of the facial artery in a 78 years old female. She presented with swelling left side of the neck who underwent further imaging including CT angiography which revealed an aneurysm of left facial artery. She was successfully treated with coiling.